Islamic and Customary Law in Aceh Darussalam Constitution - Gunawan Adnan (Heritage of Nusantara: International Journal of Religious Literature and Heritage, 2013)
It is confessed that the relationship between Islamic taw and customary law in Aceh is very tight and hardly distinguished. This phenomenon hold also true and could be traced through the canonical texts of Aceh Darussalam kingdom. This articIe is aimed at examining this indication through a brief study on the manuscript of the so-called three laws of Aceh, especially pertaining to siyasah (politics) and the forms of relationship between the two legal systems. Furthermore, it will also discuss the substance of the text compared with al-Mawardi's thought in al-Ahkam al-Sulthaniyyah. The study safely comes to the conclusion that the majority of siyasah concept of Islamic law has been absorbed into the structure of canonical texts of Aceh Darussalam Kingdom. Last but not least, it is also found two forms of absorption, namely, total and selective absorptions.